2014
DOI: 10.1177/1742271x14565504
|View full text |Cite
|
Sign up to set email alerts
|

Can interactive educational technologies support the link between ultrasound theory and practice via feedback mechanisms?

Abstract: Linking theory to practice is an area of concern for ultrasound students, clinical mentors and academic staff. The link between theory and practice requires a robust clinical mentorship scheme in addition to careful curricula design considerations to improve student outcomes. The introduction of interactive technology in education provides ripe opportunity to improve feedback to students to support the link between theory and practice. A series of three interactive learning and teaching activities were designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The vLAB cannot completely replace practical training but it can bridge the theory-practice gap. According to Dickson [26], interactive technologies can bridge the theory-practice gap within ultrasound teaching through the recurring feedback it can give students. A study showed that using a vLAB in the field of gynaecological ultrasound was good preparation for clinical practice [25].…”
Section: Discussionmentioning
confidence: 99%
“…The vLAB cannot completely replace practical training but it can bridge the theory-practice gap. According to Dickson [26], interactive technologies can bridge the theory-practice gap within ultrasound teaching through the recurring feedback it can give students. A study showed that using a vLAB in the field of gynaecological ultrasound was good preparation for clinical practice [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that little research has been undertaken to date evaluating the effectiveness of ultrasound simulation in healthcare education (Dickson, 2015;Gibbs, 2014 and. However, the positive impact on the student experience is recognised, as is the increase in student's confidence when they subsequently attended the clinical placement (Gibbs, 2014 andMartin, 2014;Reid-Searl, Bowman, McAllister, Cowling, & Spuur, 2014).…”
Section: Educational Modelmentioning
confidence: 99%
“…Attempts to supplement this with ultrasound simulation have been trialled and are currently being evaluated further. It is acknowledged that little research has been undertaken to date evaluating the effectiveness of ultrasound simulation in healthcare education (Gibbs, 2014;Dickson, 2015 andGibbs, 2015). However, the positive impact on the student experience is recognised as is the increase in student's confidence when they subsequently attended the clinical placement (Gibbs, 2014;Martin, 2014 andGibbs, 2015).…”
Section: P4 You Couldn't Just Have Them Step Into a Band 7 As A Newlymentioning
confidence: 99%